Hubungan antara Bank umum dan Microfinance dalam Alokasi Kredit pada Usaha Mikro, Kecil dan Menengah (UMKM) - Christian Herdinata (Jurnal Riset Manajemen dan Bisnis, 2008)
Small Medium Enterprises (sl"frg always complain about the rigidity of entrance (accessibility) of *ternal funds especially from banking. Economics rqtort of Indonesia done by the Indonesia Bonk noted thot the LDR ratio of the commercial banb in the yem of 2007 showed that the number was for under 100%, i.e. 69.2%o, while the rotio of LDR of BPRwas more than t00ok, i.e. 109.73%. Thisfact aplained that the publicfund mustered by the commercial bank sfill remained to be able to be channeled in credit, while BpR has gone beyondfunds which ought to be channeled in theform of credit. This indiccted that itfailed in allocation of credit. Therefore, this research, which was based on critical revievrt of literature and idea, indicoted that the business scale determined the pattem of the relationship of microfinance otd thefunction of intermediation *periences failed in fficiently *ecuting allocation of credit.  Therefore, constructing a relatiowhip between the commercial bank and mierofinance and sMEs was badly needed, not to irwite a.rymmetries ofinformafion but to effrcient$t allocate the credit.Keywords: Small Medium Enterprises (SMEs), allocation of credit, ratio of LDR